Secure Relationship does not mean Satisfying Relationship during the Pandemic: The Role of Mattering and Life Satisfaction - Hong Chun Yeoh; Susanna Lin Hong Poay; Kususanto Ditto Prihadi; Endah Kurniawati Purwaningtyas (International Journal of Public Health Science (IJPHS), 2022)
Relationship satisfaction is one of major component of mental health that often ignored by mental health practiticoners in general due to cultural reasons. Moreover, because numerous studies had indicated that when individuals have insecure attachment styles (insecurity in loving someone else), they would never develop any relationship satisfaction with anyone, including friends, spouses, parents, children, ans relatives. Th COVID-19 pandemic had triggered different social patterns among individuals all over the world, and studies during the pandemic indicated the significance of some factors such as the sense of mattering and perceived life satisfaction to the mental health of the general adults. Our references led us to hypothesize that the interpersonal mattering significantly predicts relationship satisfaction, mediated by life satisfaction, under the condition of low secure attachment style. Randomly selected 405 adults from Kuala Lumpur and Selangor, Malaysia, were financially compensated to complete the scales of interpersonal mattering, satisfaction with life, secure attachment style section of MOAS, and relationship satisfaction index. The results indicated that the mediation of life satisfaction on the link between mattering and relationship satisfaction was only significant when the level of secure attachment style is at the low and moderate levels. Further implications, limitations, and suggestions are discussed